2012
DOI: 10.21913/ijei.v8i2.811
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of Iranian EFL Masters students' perceptions of plagiarism

Abstract: This study examined the understanding, perceived seriousness, and prevalence rates of different forms of plagiarism among Iranian English as a Foreign Language (EFL) Masters students studying at universities in Iran where their courses were taught in English. A survey questionnaire was used. The results indicated that plagiarism was pervasive among the students, and that they had an inadequate understanding of different forms of plagiarism. Second, prevalence rates of plagiarism were negatively correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
4
24
0
3
Order By: Relevance
“…In addition, one of the researchers also works as an Assistant Librarian at MZUNI where he has observed that some postgraduate students' theses contain poor attribution to sources and the list of references are poorly prepared or completely omitted. Third, literature shows that students cannot be completely blamed for committing plagiarism because some may commit this academic offence unintentionally (Batane 2010;Mahmood et al 2011;Zafarghandi et al 2012). Finally, our thorough search in major library databases reveals that no research has been conducted in relation to plagiarism in higher education in Malawi.…”
Section: Problem Statement and Research Questionsmentioning
confidence: 93%
See 4 more Smart Citations
“…In addition, one of the researchers also works as an Assistant Librarian at MZUNI where he has observed that some postgraduate students' theses contain poor attribution to sources and the list of references are poorly prepared or completely omitted. Third, literature shows that students cannot be completely blamed for committing plagiarism because some may commit this academic offence unintentionally (Batane 2010;Mahmood et al 2011;Zafarghandi et al 2012). Finally, our thorough search in major library databases reveals that no research has been conducted in relation to plagiarism in higher education in Malawi.…”
Section: Problem Statement and Research Questionsmentioning
confidence: 93%
“…The danger with students overrating their academic writing is that they may not appreciate deficiencies in their academic writing abilities, and consequently, they may continue to commit plagiarism unintentionally. Poor understanding of plagiarism on the part of students put them at a higher risk of plagiarising (Leask 2006;Mahmood et al 2011;Orim et al 2013;Riasati and Rahimi 2013;Zafarghandi et al 2012).…”
Section: Brief Review Of Related Literaturementioning
confidence: 99%
See 3 more Smart Citations